Knowledge management initiative: a case study in Malaysia National Library - Yaacob, Nurul Ibtisam; Abdullatif, Zaidoon Kh.; Osama, Khalid; Nasser Avif, Mustafa; Abdulghani, Montadzah Ambag; Ahmad Dahlan, Abdul Rahman; Ahmad, Nafisah (State Islamic University Syarif Hidayatul Jakarta, 2010)
The Malaysia National Library (PNM) was established in 1966 as a unit of the National Archives of Malaysia. Today PNM is a Division under the Ministry of Information, communications and Culture. PNM plays a significant role in collecting, processing, disseminating, storing and utilizing knowledge. This role is parallel with the aspiration of Malaysia government to inculcate a knowledge culture in the development of Malaysia and to promote a reading culture among Malaysians. So far, PNM does not really have a system in managing their knowledge. This paper tries to propose a Knowledge Management (KM) model that suits with PNM situation, which later could be used in fully applying and implementing KM in PNM.